MENGGALI PARADIGMA PENDIDIKAN BERKEADABAN DARI KITAB AYYUHA AL-WALAD DAN KIMIATUS SA’ADAH - Rahem, Zaitur (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2018)
Portrait of education in the homeland, one side shows the achievements to be proud of. A number of developments in education can move with the rhythm of the times. Material, procedural education in Indonesia increasingly steady occupy its position. However, on the other hand, there are a number of issues that have not been completed yet. Among these issues are character, education professionalism, organizational governance professionalism, and maximization of learning. These issues become big obstacles / challenges posed a serious threat in the course of the Indonesian education world. The bid of theory, including the release of Imam al-Ghazali's thought in his two books ايها الولد and كيمياء السعا دة, in the review of this article becomes the point of view as an alternative conceptual offer in addressing existing educational problems. Although the review in this article's review is conceptual-research, the author compiles Imam al-Ghazali's thought with the real context of the homeland education issue. According to Imam al-Ghazali in the study of ايها الولد and كيمياء السعا دة, character education begins early without regard to the limit of formality. As a result, the thought of this medieval clergy remained synergistic and became a necessary issue as a solution to the problem of education in Indonesia.